Phytochemical Study of Green Meniran Herb (Phyllanthus niruri L.) and Red Meniran Herb (Phyllanthus urinaria L.) in Jekan Raya Sub-district of Palangka Raya City, Central Kalimantan Province - Damiti, Sukmawati; Mashar, Harlyanti Muthma’innah; Yusuf, Baharuddin (Journal of Experimental and Clinical Pharmacy (JECP), 2024)
Kalimantan is one of the islands in Indonesia that is famous for its rich biodiversity. Knowledge about the use of traditional medicine using plants has been passed down from generation to generation among the ethnic natives of Kalimantan. One of the typical Kalimantan plants that is efficacious as traditional medicine and contains various potential secondary metabolites is meniran. Based on ethnobotanical studies in Central Kalimantan, meniran is boiled to treat fever, dysentery, jaundice, malaria, therefore further research is needed for the chemical content of meniran which is efficacious. This study aims to determine the phytochemical of green meniran herb (Phyllanthus niruri L.) and red meniran herb (Phyllanthus urinaria L.). Determination of plant samples was carried out for both types of meniran. Then processing, extraction and identification of chemical content. The yield values of each extract obtained were 7.40% and 8.76%. As for the results of phytochemical studies, green and red meniran herb both contain alkaloid, tannins and flavanoids, but green meniran is indicated to have steroid content and red meniran contains triterpenes. Secondary metabolites possessed by these two types of meniran plants are beneficial for health, including as antioxidants, antibacterial, antiviral, anticancer and a number of pharmacological activities that are significant in improving one's health and minimizing the risk of infection by pathogens. However, further research is needed to test the activity of the content of these two types of meniran as a basis for the manufacture of traditional medicines.